Recurring mammary ductal ectasia in children: Case report - Durriyah D. Sinno; Farah Faytrouni; Ghina Berjawi; Hala Tfeily (Elsevier, 2017)
Bloody nipple discharge is a rare finding in children; its occurrence in infants is almost always benign in origin and suggests primarily the presence of mammary ductal ectasia. We describe the case of a 4 years 6 months old male child who presents with right bloody nipple discharge and no other associated symptoms. Blood tests were normal. Ultrasound revealed mammary ductal ectasia. Symptoms resolved spontaneously after 6 months. After 3 years, the patient presented again for the same complaint, but in the contralateral breast and mammary ductal ectasia recurrence was found. Histological findings, characteristics, recurrence and available treatments of ductal ectasia will be discussed.